Lower Serum Free Amino Acids in Holstein Cows with Milk Fever in Field Case - Kudo Katsunori; Ohtsuka Hiromichi (Acta Veterinaria)
This study was conducted to investigate the relationship between serum free amino acids (FAA) and the onset of milk fever in dairy cows around the time of calving. The serum concentration of FAA was compared between multiparous cows with milk fever (MF group; n=7) and healthy multiparous cows (Control Group; N=16) kept on a Holstein dairy farm. Blood samples were obtained 3 to 4 weeks prepartum, on the day of calving, and 1 month post partum for analysis of serum amino acids and lipid parameters. The levels of all essential amino acids in the MF group were lower than those in the Control group. Significant differences between groups were observed in phenylalanine, valine, isoleucine, and leucine at 1 month post partum, and in tryptophan on the day of calving. Regarding the non essential amino acids, a significantly lower level of arginine was observed in the MF group compared to the Control group on the day of caving, as well as 1 month post partum. A significant positive correlation was detected between cholesterol and branched chain amino acids (BCAA) levels (r=0.531, P<0.01). These results showed that MF cows had lower levels in several FAA around the time of calving even before the onset of MF.